Clogging in Low Reynolds Number Channel Flow. - Holway, Sydney W. (Tufts Archival Research Center, 2018)
The mechanisms behind particulate clogging are probed by observing microfluidic channel clogging with high speed video microscopy. Results indicate the absence of a dilute-to-dense transition in the low Reynolds number regime, and indicate that steric exclusion at the channel walls causes particulate depletion as flow enters the throat of the channel constrictions.